Discovery of bicyclic borane molecule B14H26 - Xiaoni Zhang; Tomoko Fujino; Yasunobu Ando; Yuki Tsujikawa; Tianle Wang; Takeru Nakashima; Haruto Sakurai; Kazuki Yamaguchi; Masafumi Horio; Hatsumi Mori; Jun Yoshinobu; Takahiro Kondo; et al. (Communications Chemistry)
Abstract The discovery of fullerene following the synthesis of graphene marked a paradigm shift in chemistry. Here, we report the discovery of biycycloborane, arising from the synthesis of borophane (hydrogen boride). Uniquely, this synthesis method involves a decomposition mechanism rather than traditional atom-by-atom assembly, marking an unique approach to constructing complex borane structures. The mass spectrometry unveiled that the stable molecule has a mass of 178 in atomic mass unit with a stoichiometry of B14H26. Optical spectra and simulations further evidenced its bicyclic structure, featuring fulvene-like heptagons or octagons. This borane molecule, analogous to cyclic hydrocarbons, adopts a unit configuration with a three-center two-electron (3c-2e) bonding, akin to diborane. The B14H26 molecule has been historically anticipated as a distant descendant of the dodecahedron borane, but it was born from the hydrogen boride sheet with a non-symmorphic symmetry. The discovery of biycycloborane expands the frontiers of boron chemistry, promising advancements in boron-based nanomaterials and beyond.